An integrated framework for the optimisation of sport and athlete development: A practitioner approach - Gulbin, J. P.; Croser, M. J.; Morley, E. J.; Weissensteiner, J. R. (Journal of Sports Sciences, 2013)
This paper introduces a new sport and athlete development framework that has been generated by multidisciplinary sport practitioners. By combining current theoretical research perspectives with extensive empirical observations from one of the world's leading sport agencies, the proposed FTEM (Foundations, Talent, Elite, Mastery) framework offers broad utility to researchers and sporting stakeholders alike. FTEM is unique in comparison with alternative models and frameworks, because it: integrates general and specialised phases of development for participants within the active lifestyle, sport participation and sport excellence pathways; typically doubles the number of developmental phases (n = 10) in order to better understand athlete transition; avoids chronological and training prescriptions; more optimally establishes a continuum between participation and elite; and allows full inclusion of many developmental support drivers at the sport and system levels. The FTEM framework offers a viable and more flexible alternative for those sporting stakeholders interested in managing, optimising, and researching sport and athlete development pathways.